2016
DOI: 10.1111/ijd.13046
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Staphylococcus aureus isolated from skin infections and its implications in various clinical conditions in Korea

Abstract: The prevalence of MRSA in skin infections in South Korea did not increase during 2010-2013. Isolates from dermatology outpatients showed relatively lower rates of resistance to multiple antimicrobials than isolates from non-dermatology outpatients. Among topical antimicrobials, resistance to mupirocin was relatively low regardless of clinical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Of note, the overuse of erythromycin, which is often prescribed for impetigo therapy in China [ 27 ], may be the primary reason why the high level of resistance happened. Moreover, besides erythromycin, resistance to all the other tested macrolide antibiotics among MSSA isolates was significantly lower than that of MRSA isolates (Table 1 ), which was similar with early report [ 28 ]. These results also demonstrated that S. aureus co-holding macrolide resistance and virulence determinants in the hospitals would be prevalence.…”
Section: Discussionsupporting
confidence: 90%
“…Of note, the overuse of erythromycin, which is often prescribed for impetigo therapy in China [ 27 ], may be the primary reason why the high level of resistance happened. Moreover, besides erythromycin, resistance to all the other tested macrolide antibiotics among MSSA isolates was significantly lower than that of MRSA isolates (Table 1 ), which was similar with early report [ 28 ]. These results also demonstrated that S. aureus co-holding macrolide resistance and virulence determinants in the hospitals would be prevalence.…”
Section: Discussionsupporting
confidence: 90%
“…MRSA isolates possess an MGE called staphylococcal cassette chromosome mec, which carries methicillin resistance gene (ie, mecA ) and several other genes conferring resistance to non-beta-lactam antibiotics and is in charge of MDR in MRSA isolates 32. This phenomenon results in the diminished efficacy of most antimicrobial agents in the eradication of MRSA infections and can complicate the selection of proper therapeutic regimens for them 33,34…”
Section: Discussionmentioning
confidence: 99%
“…The following 19 antimicrobials were tested: clindamycin; ciprofloxacin; erythromycin; fusidic acid; nitrofurantoin; gentamicin; habekacin; linezolid; mupirocin; oxacillin; penicillin; quinupristin/dalfopristin; rifampicin; trimethoprim/sulfamethoxazole (TMP‐SMX); telithryomycin; tetracycline; tigecycline; teicoplanin; and vancomycin. Resistance to oxacillin was considered equivalent to resistance to methicillin. Quality control was performed by testing a standard S. aureus strain (ATCC29213).…”
Section: Methodsmentioning
confidence: 99%
“…Methicillin‐resistant Staphylococcus aureus (MRSA) has been considered a pathogen of great concern because of the burden of serious disease associated with infection. In addition to relatively mild skin and soft‐tissue infections, MRSA can cause life‐threatening pneumonia and sepsis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation